Seroprevalence of cystic echinococcosis in a high-risk area (Al-Mafraq Governorate) in Jordan, using indirect hemagglutination test. (May 2019) - Himsawi, Nisreen; Hijjawi, Nawal; Al-Radaideh, Ali; Al-Tamimi, Mohammad
Abstract: Hydatid disease (HD) is a zoonotic disease of humans and animals which is caused by infection with the larval stages of the taeniid cestodes of the genus Echinococcus . HD is endemic in many countries of the Middle East, including Jordan. The seroprevalence rate of HD in areas of elevated risk in Jordan has not previously been investigated using indirect haemagglutination (IHA) testing. In the present study, 512 blood samples were collected from recruited outpatients from an internal medicine clinic in Al-Mafraq Governmental Hospital in Jordan. Each participant signed a consent form and completed a questionnaire. The presence of antibodies specific for E. granulosus antigens was detected using an IHA test. Statistical analysis was performed by SPSS software using the Chi-square test. In all, 4.1% of the study participants were seropositive for E. granulosus IgG antibodies. There was a significant correlation between unexplained weight loss among seropositive patients ( P  = 0.018). Seropositivity was significantly higher in patients who slaughtered sheep inside their houses ( P  = 0.023). HD seroprevalence did not correlate with gender ( P  = 0.433), age ( P  = 0.880), residency status ( P  = 0.938), or educational level ( P  = 0.808). The vast majority (75.2%) of participants reported no prior knowledge about HD, and 99.8% were not aware about the etiology of the disease.